SBS-suppression in variably strained fibers for fiber-amplifiers and fiber-lasers with a high spectral power density - Engelbrecht, Rainer; Hagen, J; Schmidt, M (XV Int. Symp. on Gas Flow, Chemical Lasers and High-power Lasers, GCL/HPL 2004, Prague. Proceedings of SPIE, 2005)
Stimulated Brillouin-Scattering (SBS) limits the spectral power density of fiber amplifiers and lasers. Theory and measurements of SBS in fibers with a defined strain distribution are presented. SBS threshold was increased by a factor of 2
lhft_intern.bib::engelbrecht04e